Output speed prediction of an overrunning clutch for oscillatory input motion using a simplified approach - Mokhlis, M.M. (EDP Sciences, 2014)
This paper presents the derivation of a simplified mathematical equation to predict the output speed of an overrunning clutch. The working principle of the overrunning clutch was studied and mathematical equations were derived for different cases. A MATLAB Simulink model was created to simulate the equations and ADAMS/View simulation was used for verification. The equations are able to calculate the output motion with minimal errors. The equation can be used for a quick estimation to predict the output speed for any kind of input motions. Â© 2014 Owned by the authors, published by EDP Sciences.